Association of liver enzymes and lipid profile with body fat distribution in Mexican university students - Valbuena-Gregorio, Edith; López-Mata, Marco Antonio; Olivas-Aguirre, Francisco Javier; Márquez-Ibarra, Adriana Alejandra; Armenta-Guirado, Brianda Joanna; Arreguín Coronado, Andrea (Archivos Latinoamericanos de Nutrición (ALAN), 2025)
Introduction: Evidence suggests that the type of adipose tissue distribution contributes to a higher risk of developing cardiovascular diseases. It has been observed that visceral adipose tissue is highly lipolytic, and lipid distribution is primarily directed towards the liver, resulting in an excessive flow of fatty acids that can trigger lipid alterations and a high risk of hepatic steatosis. Objective: This study aimed to find the association of liver enzymes and lipid profile with body fat distribution in Mexico university students. Materials and methods: Cross-sectional, descriptive, and correlational study with a sample of university students aged 18 to 26 years. Anthropometric measurements, a 24-hour dietary recall (R24h), Pittsburgh sleep quality index, body fat determination, DXA-derived visceral adipose tissue (cm²) and subcutaneous adipose tissue (g), and blood samples were collected to determine lipid profile (low-density lipoprotein [LDL], high- density lipoprotein [HDL], very low-density lipoprotein [VLDL], triglycerides [TG], total cholesterol [TC]) and liver enzymes (aspartate aminotransferase [AST], alanine aminotransferase [ALT], and gamma-glutamyl transferase [-GT]). Results: We found a positive association between the type of fat distribution and LDL, VLDL, TC, TG, ALT, and -GT, indicating that higher visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), and body mass index (BMI) increase the concentrations of these biochemical parameters. In contrast, HDL showed a negative association, decreasing with an increase in VAT, SAT, and BMI. Conclusions: Body fat distribution (VAT and SAT) influences the lipid (LDL, VLDL, TC, TG, and HDL) and liver (ALT and -GT) levels of university students, which may indicate metabolic alterations. Introducción: La evidencia sugiere que el tipo de distribución del tejido adiposo contribuye a un mayor riesgo de desarrollar enfermedades cardiovasculares. Se ha observado que el tejido adiposo visceral es altamente lipolítico, y la distribución de lípidos se dirige principalmente hacia el hígado, lo que resulta en un flujo excesivo de ácidos grasos que puede desencadenar alteraciones lipídicas y un alto riesgo de esteatosis hepática. Objetivos: Este estudio tuvo como objetivo determinar la asociación entre las enzimas hepáticas y el perfil lipídico con la distribución de grasa corporal en estudiantes universitarios de México. Materiales y métodos: Estudio transversal, descriptivo y correlacional con una muestra de estudiantes universitarios de 18 a 26 años. Se realizaron mediciones antropométricas, un recordatorio dietético de 24 horas (R24h), índice de calidad del sueño de Pittsburgh, determinación de grasa corporal, tejido adiposo visceral (cm²) y tejido adiposo subcutáneo (g) derivados de DXA, y se tomó muestra de sangre para determinar el perfil lipídico (lipoproteínas de baja densidad [LDL], lipoproteínas de alta densidad [HDL], lipoproteínas de muy baja densidad [VLDL], triglicéridos [TG], colesterol total [CT]) y enzimas hepáticas (aspartato aminotransferasa [AST], alanina aminotransferasa [ALT] y gamma-glutamil transferasa [-GT]). Resultados: Encontramos una asociación positiva entre el tipo de distribución de la grasa y LDL, VLDL, TC, TG, ALT y -GT, indicando que un mayor tejido adiposo visceral (TAV), tejido adiposo subcutáneo (TAS) e índice de masa corporal (IMC), aumentan las concentraciones de los parámetros bioquímicos. En cambio, la HDL mostró una asociación negativa, disminuyendo con el aumento del TAV, el TAS e IMC. Conclusiones: La distribución de la grasa corporal (TAV y TAS) influye en los niveles lipídicos (LDL, VLDL, TC, TG y HDL) y enzimas hepáticas (ALT y -GT) de los estudiantes universitarios, lo que puede indicar alteraciones metabólicas.